The Development and Evaluation of a Culturally Appropriate Home-based Intervention for Children with Autism Spectrum Disorders in the Kingdom of Saudi Arabia - Alanazi, Hissah Hajaj (Curtin University, 2022)
The limited research regarding Autism Spectrum Disorders (ASD) within the Kingdom of Saudi Arabia (KSA) suggests a serious lack of understanding of the disorder, a scarcity of ASD services, and few trained professionals. In addition, there are few studies of evidence-based practices to support families of children with ASD which are culturally appropriate in KSA. Research on families’ experiences of raising children with ASD indicated an urgent need for professional support. Home-based interventions (HBIs) administered by parents of children with ASD have been found to be an effective method to receive ASD services within the naturalised home environment. The purpose of this project was to develop and evaluate a culturally appropriate HBI to support families and their children with ASD in KSA.